Teicoplanin usage in adult patients with haematological malignancy in the UK and Ireland: Is there scope for improvement?. Issue 5 (15th April 2014) - Byrne, Catherine J; Egan, Sean; D'Arcy, Deirdre M; O'Byrne, Philomena; Deasy, Evelyn; Fennell, Jérôme P; Enright, Helen; McHugh, Johnny; Ryder, Sheila A
Abstract : Objective: To investigate current practices with teicoplanin in patients with haematological malignancy in centres throughout the UK and Ireland with respect to indication for usage and timing of introduction in febrile neutropenia, dosage regimens and therapeutic drug monitoring practices. Methods: An online survey was distributed to 598 haematology and oncology pharmacists representing 168 institutions throughout the UK and Ireland. Survey questions were aimed at identifying typical hospital practices for teicoplanin use specifically in patients with haematological malignancy in terms of empiric use strategies, dosage regimens and therapeutic drug monitoring. Participants were asked to base their answers on actual practice or policy in their hospitals and not on personal opinions. Results: A total of 51 pharmacists participated in the survey. Responses indicated that teicoplanin is widely used in adult patients with haematological malignancy in the UK and Ireland, but evidence–practice gaps for empiric use strategies in febrile neutropenia were noted. For dose selection, the manufacturer's Summary of Product Characteristics was heavily relied upon in UK and Irish institutions, rather than therapeutic drug monitoring, as an indicator of therapeutic dosing. Conclusions: Despite emerging evidence to support targeted prescribing, aggressive dosing and routine therapeutic drug monitoring, findings suggest that many centres do not use teicoplanin in this way. The findings suggest inappropriate use of teicoplanin in these patients. Improving the translation of available evidence into regular practice may improve patient outcomes and reduce unnecessary teicoplanin usage. Pharmacists could aid this process through education and increased involvement in drug therapy decisions.